ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DALAM MENINGKATKAN PENGENDALIAN INTERN PENJUALAN PADA PT. GUNUNG SELAMAT LESTARI LABUHAN BATU SELATAN - Martha S. P. Simanjuntak; Dimita Hemalli Premasari Purba; Mitha Christina Ginting (Universitas Methodist Indonesia, 2019)
The purpose of this research is to find and analyze information system accounting sales to increase internal control sales in PT. Gunung Selamat Lestari Labuhanbatu Selatan in 2017-2018. The kind of data used in this research was secondary data. The data source of the document PT. Gunung Selamat Lestari Labuhanbatu Selatan of history that company, the structure of the organization picture and accounting sales information system. Technique analysis of the data used is the method descriptive. Based on the discussion of the results research known parts involved in sales in PT. Gunung Selamat Lestari Labuhanbatu Selatan is buyers, sales division, part KTU or administration, a part of the barn, part bookkeeping. Function related in accounting sales information system is a function sales, function the warehouse and function bookkeeping. Inform system Accounting information system sales to increase sales in PT. Gunung Selamat Lestari Labuhanbatu Selatan has not materialized effectively and efficiently.